The Importance of Cooperation Between Physicians and Dentists in the Recognition and Management of Undiagnosed and Uncontrolled Diabetes: A Critical Need During the COVID19 Pandemic - Farinaz Noorbakhsh; Mahdieh Vahedi; Hayedeh Pazhand Birjandi (Reviews in Clinical Medicine)
AbstractBackground: Diabetes mellitus (DM) is one of the most common metabolic disorders. Its pathogenesis involves a combination of anatomical and biochemical abnormalities. Type 2 diabetes exhibits a genetic predisposition, while type 1 diabetes has an idiopathic, autoimmune background. Dentists can play a crucial role in the early diagnosis and identification of uncontrolled diabetes. Chronic inflammation and infections in the oral cavity can significantly impact disease management. Therefore, any dental lesions or gingival alterations, including periodontitis, must be treated promptly. After taking a thorough medical and dental history of suspicious cases, appropriate diagnostic tests should be conducted, or the patient should be referred to a physician. Early diagnosis of diabetes is instrumental in preventing both acute and chronic complications. Additionally, patients with diabetes are at a higher risk of developing severe illness if infected with the novel coronavirus (COVID-19). The aim of this article is to share the latest information about the two types of diabetes and to highlight how dentists can contribute to their management.Method and Materials: This article provides a compact overview of relevant articles and books published from 2014 to 2024.Conclusion: Dentists play a vital role in the early diagnosis of diabetes and in identifying uncontrolled or poorly controlled cases. Close cooperation between healthcare providers and dentists is essential for effective diabetes management. This collaboration was particularly important during the COVID-19 pandemic.